(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
The article presents the results of a theoretical analysis of the features of the organization and methods of conducting swimming lessons for students. The main tasks and problematic issues of organizing swimming. The results of a questionnaire survey and analysis of the protocol of results of determining the level of swimming readiness of first-year students are given.